Տնտեսության նոր հնարավորություններ՝ հիմնված «մեծածավալ տվյալների» վրա - Ն. Հ. Մանուկյան (ՀՀ ԳԱԱ հրատ.)
Последние несколько лет информационные технологии переходят на новую платформу, в основе которой лежат облачные, мобильные, социальные технологии и технологии ”больших данных” и аналитики. ”Большие данные” и интернет “вещей” создают широкие возможности для решения глобальных социальных и экономических проблем. For the past few years there has been a transition of the information technologies to a new platform which is based on cloud computing, mobile and social technologies as well as technologies of big data and analysis. The big data and the internet of "things" trigger enormous opportunities for the solution of global, social and economic problems.
Keywords: H Social Sciences; Economic Theory; Information resources; Bibliography